Pengaruh Kualitas Laporan Keuangan Terhadap Akuntabilitas Kinerja Pada instansi Pemerintah di Bidang Pendapatan Daerah Provinsi Sulawesi Selatan - Sudirman abdi; Rahmi Rahmi (Fakultas Ekonomi Universitas Indonesia Timur, 2022)
The purpose of this study was to determine the effect of the quality of financial reports on performance accountability in government agencies in the Regional Revenue Agency of South Sulawesi Province. This sample was taken from the Office of Regional Revenue of South Sulawesi Province. The type of data used in this study is quantitative data obtained from questionnaires distributed and related to the problem under study. Data collection was carried out by observation and distributing questionnaires. In this study the data sources used in data collection include primary data and secondary data. The research instrument used in this study used a Likert scale. Based on the results of data research using statistical calculations through the application of the Statistical Package for the Social Science (SPSS) version 25 regarding the Effect of Quality Financial Reports on Performance Accountability in Government agencies in the Regional Revenue Sector of South Sulawesi Province which has been discussed in the previous chapter, the authors draw important conclusions namely the quality of financial reports (X) significantly affects the performance accountability of government agencies (Y) at the Regional Revenue Agency of South Sulawesi Province, this indicates that Ho (Nil hypothesis) has no rejected effect and Ha (Alternative Hypothesis) has an accepted effect.